2018
DOI: 10.3389/fimmu.2017.01925
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CD4 and CD8 T-Cell Subsets and Inflammatory Biomarkers during Early and Chronic HIV Infection in Mozambican Adults

Abstract: During primary HIV infection (PHI), there is a striking cascade response of inflammatory cytokines and many cells of the immune system show altered frequencies and signs of extensive activation. These changes have been shown to have a relevant role in predicting disease progression; however, the challenges of identifying PHI have resulted in a lack of critical information about the dynamics of early pathogenic events. We studied soluble inflammatory biomarkers and changes in T-cell subsets in individuals at PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 66 publications
2
37
0
1
Order By: Relevance
“…Studies conducted in nonhuman primates and humans demonstrated that HIV-1/ SIV-1 preferentially infects highly mature subsets, causing a reduction in their frequencies during the acute phase of the disease. At the same time, less differentiated subsets, such as naive cells and CM, are less likely to be infected but can be stimulated to proliferate and expand (3,(25)(26)(27)(28). In line with these findings, we found that the frequencies of naive cells, SCM, and CM remain elevated during the late acute HIV-1 infection, whereas those of EM and TE progressively decrease.…”
Section: Discussionsupporting
confidence: 84%
“…Studies conducted in nonhuman primates and humans demonstrated that HIV-1/ SIV-1 preferentially infects highly mature subsets, causing a reduction in their frequencies during the acute phase of the disease. At the same time, less differentiated subsets, such as naive cells and CM, are less likely to be infected but can be stimulated to proliferate and expand (3,(25)(26)(27)(28). In line with these findings, we found that the frequencies of naive cells, SCM, and CM remain elevated during the late acute HIV-1 infection, whereas those of EM and TE progressively decrease.…”
Section: Discussionsupporting
confidence: 84%
“…LPS, sCD14, IL6 and IP10 are some of the plasma biomarkers that have been shown to be elevated in HIV patients [7, 47]. In fact, these inflammatory biomarkers are reliable predictors of HIV disease progression correlating consistently with CD4 decline and plasma viral load [3, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TLR9 stimulation via CpG has been shown to induce IP10 production from monocytes, plasmacytoid dendritic cells and B cells [49, 50]. Interestingly, IP10 has been shown to be elevated in HIV infections [7, 47] and associated with CD4 decline [65], immune activation [66] and plasma viral load [65]. Recent studies have also shown IP10 to be a highly sensitive marker of viremia in acute HIV infections [52, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have associated the elevated immune activation with CD4 + T cell depletion and progression to AIDS [27]. During primary HIV-1 infection (PHI), viral loads can reach values higher than one million HIV-1 RNA copies/mL, and a significant decrease in CD4 + T cell counts occurs [8, 9]. A high production of pro-inflammatory cytokines, called a “cytokine storm”, arises in response to virus replication [10].…”
Section: Introductionmentioning
confidence: 99%